PENGARUH KREDIT USAHA KECIL (KUK) TERHADAP PERKEMBANGAN PRODUKSI DAN TENAGA KERJA PADA USAHA KECIL DI SUMATERA BARAT - Selly Prima Desweni (Ensiklopedia of Journal, 2019)
This study aims to analyze: (1) Effect of Micro Business Credit (KUK) on the number of Micro business production in West Sumatra. (2) Effect of Micro Business Credit (KUK) on the number of workers in West Sumatra. This type of research is descriptive and associative research, namely research that describes the research variable and finds the presence or absence of influence between independent variables and dependent variables. The type of research data is secondary data which is processed using statistical analysis. The results of this study: (1) Micro Business Credit (KUK) has a significant influence on the number of small business production in West Sumatra. This means that the greater the number of Micro Business Loans (KUK) channeled by banks, the greater the possibility that the number of micro business production will increase, (2) Micro Business Credit (KUK) has a significant influence on the number of small business workers in West Sumatra. This means that the greater the number of Micro Business Loans (KUK) channeled by banks, the greater the possibility that the number ofmicro business workers will increase. The author advises banks to increase the number of mivro Business Loans (KUK) to small entrepreneurs, so that later small entrepreneurs can increase the amount of production and use of labor, this is likely to improve the economy in West Sumatra. Keywords: Micro Business Credit (KUK), Micro business production, labor